Occurrence of feline leukemia feline immunodeficiency in domestic cats from the municipality of Mineiros, Goiás - Ramos, Dirceu; Lemos, Marinara; Oliveira, Juciene; Almeida, Sabrina; Oliveira, Priscila; Ferraz, Henrique; Toledo Lopes, Dyomar; Casaro Saturnino, Klaus; Borges, Karla; Braga, Ísis (Pubvet, 2019)
The feline leukemia virus (FeLV) and the feline immunodeficiency virus (FIV) belong to the Retroviridae family and are important agents as they affect the immune system of felines. The objective of this study was to evaluate the occurrence of FIV and FeLV in cats from the municipality of Mineiros, in the Goiás state, randomly selected. Seventy-two cats from the municipality of Mineiros were randomly evaluated using the ALERE™ FIV Ac / FeLV Ag TEST KIT chromatographic test, and of these 12.5% showed reagents to FIV and 2.77% to FeLV, with a higher frequency of infection in male cats, both adults and non-defined, who had free access to the street, which is a very relevant factor in the spread of FIV and FeLV, given their mode of transmission. Studies on the epidemiological investigation of these viral diseases in the region are scarce, but the data obtained in this area provide relevant information to the city’s professionals, so that they can guide the owners, seeking control of the diseases in the animals.